Inhibition of Cellular Proteasome Activities Mediates HBX-Independent Hepatitis B Virus Replication In Vivo - Zhang, Zhensheng (American Society for Microbiology (ASM), 2010)
The X protein (HBX) of the hepatitis B virus (HBV) is essential for HBV productive infection in vivo. Our previous study (Z. Hu, Z. Zhang, E. Doo, O. Coux, A. L. Goldberg, and T. J. Liang, J. Virol. 73:7231-7240, 1999) shows that interaction of HBX with the proteasome complex may underlie the pleiotropic functions of HBX. Previously, we demonstrated that HBX affects hepadnaviral replication through a proteasome-dependent pathway in cell culture models. In the present study, we studied the effect of the proteasome inhibitor MLN-273 in two HBV mouse models. We demonstrated that administration of MLN-273 to transgenic mice containing the replication-competent HBV genome with the defective HBX gene substantially enhanced HBV replication, while the compound had a minor effect on wild-type HBV transgenic mice. Similar results were obtained by using C57BL/6 mice infected with recombinant adenoviruses expressing the replicating HBV genome. Our data suggest that HBV replication is subjected to regulation by cellular proteasome and HBX functions through the inhibition of proteasome activities to enhance HBV replication in vivo.